Developing campaigns in the context of a disaster: Content of and reactions to advertising following the earthquake in Chile on February 27, 2010. Issue 1 (2nd February 2015) - Uribe, Rodrigo; Hidalgo, Pedro; Martinez, Carolina
Abstract : Purpose: – The purpose of this paper are to determine: how disasters are used as a theme in advertising; how the public evaluates different ways of using disasters in advertising; what dimensions directly affect these evaluations; and what aspects should be taken into account by an organization that wants or need to develop a campaign after a disaster. Design/methodology/approach: – This paper presents two studies examining the relationship between catastrophes and advertising in the context of the February 2010 earthquake in Chile. The first study scrutinizes the characteristics of print ads that used this event as their main theme. The second study evaluates the reactions of consumers to different types of post-catastrophe ads. This issue was explored in a survey on the attitudes toward and credibility of these ads and in a qualitative examination, which explored the reasons for the interviewees' evaluation. Findings: – The first study identified nine types of advertisements as the most used by advertisers. The second study showed that the most common ad types had the worst evaluations by the public. In addition, the evaluation of the ads was directly related to three dimensions: opinion with regard to the advertised brand, evaluation of the ad's performance, and perception of commercial intent. Research limitations/implications: – It is important to consider some limitations of this study: this paper used only print advertising, and the sample was selected from Chilean internet users (50 percent of the population). Practical implications: – This paper provides recommendations for for-profit and non-profit organizations that need or want to effectively develop campaigns in the context of a disaster. Originality/value: – Within the context of a few studies on the development of campaigns in the context of a catastrophe, this paper seeks to test and expand upon the scarce findings in this field.